GroEL and CCT are catalytic unfoldases mediating out-of-cage polypeptide refolding without ATP - Priya, Smriti (National Academy of Sciences, 2013)
Chaperonins are cage-like complexes in which nonnative polypeptides prone to aggregation are thought to reach their native state optimally. However, they also may use ATP to unfold stably bound misfolded polypeptides and mediate the out-of-cage native refolding of large proteins. Here, we show that even without ATP and GroES, both GroEL and the eukaryotic chaperonin containing t-complex polypeptide 1 (CCT/TRiC) can unfold stable misfolded polypeptide conformers and readily release them from the access ways to the cage. Reconciling earlier disparate experimental observations to ours, we present a comprehensive model whereby following unfolding on the upper cavity, in-cage confinement is not needed for the released intermediates to slowly reach their native state in solution. As over-sticky intermediates occasionally stall the catalytic unfoldase sites, GroES mobile loops and ATP are necessary to dissociate the inhibitory species and regenerate the unfolding activity. Thus, chaperonin rings are not obligate confining antiaggregation cages. They are polypeptide unfoldases that can iteratively convert stable off-pathway conformers into functional proteins.